A CONTRIBUIÇÃO DA HERMENÊUTICA E DA FILOSOFIA DA LINGUAGEM NA ANÁLISE E FUNDAMENTAÇÃO DA INTERPRETAÇÃO E ALTERAÇÃO DO PRENOME (Revista Direito em Debate, 2020)
This work aims to analyze and to base, based on linguistic and interpretative studies, the necessity and possibility of changing the first name in the civil registry. In order to do so, we resort to the philosophical bases of speculation on the real possibility of knowledge of phenomena, a method by which one intends to understand the function of language in this process of intelligibility and its determinants. Thus, all this serves, without the intention of exhaustion of the debate, to try to elucidate a fact as complex as the change of the name, not only by the normative bias, but considering and basing itself on the pillars on which it erects knowledge. Finally, a decision of the Federal Supreme Court is presented on this subject, in order to concretize the theories studied. The method of approach is the inductive one and the research technique is the bibliographical one.